Определение точности метода фотоупругости - Тесленко, А. А. (НТУ "ХПИ", 2007)
New method of accuracy definition for the method of photoelasticity is considered in the paper. Essence of a method consists in the modelling way of accuracy determination. Accuracy is determined in comparison of initial (modelling) stresses and stresses determined in the simulated way of measurement. The stresses determined in real experiment are used as initial (modelling) stresses. The correctness of this method is investigated.
Keywords: результирующие напряжения; определение погрешности; поле напряжений; модельная технология; определение напряжений; коэффициент регуляризации